Initial thermal-hydraulic assessment by OpenFOAM and FLUENT of a subcritical irradiation facility. (June 2018) - Lomonaco, Guglielmo; Borreani, Walter; Bruzzone, Maurizio; Chersola, Davide; Firpo, Gabriele; Osipenko, Mikhail; Palmero, Marco; Panza, Fabio; Ripani, Marco; Saracco, Paolo; Viberti, Carlo Maria
Highlights: A low power ADS may be fill the gap between existing and future facilities as MYRRHA. The preliminary thermal-fluid-dynamic assessment of research ADS has been performed. The considered research ADS has been designed in the frame of EU CHANDA project. Heat removal does not seem a great challenge for all the considered conditions. Both OpenFOAM and FLUENT performed well in the simulated cases. Abstract: Aim of this work is the preliminary thermal-fluid-dynamic assessment of a subcritical system to perform integral measurements on transmutation processes, designed in the frame of EU CHANDA project: in particular, a low power Accelerator Driven System (ADS) may represent an attractive intermediate step to fill the gap between existing and future facilities like MYRRHA (or possibly EFIT). The activity finds its place within the roadmap for the evaluation of transmutation processes in ADSs, where currently measurements are performed on the zero-power ADS Guinevère at SCK·CEN (Mol, Belgium), while in the future it is expected that MYRRHA will be the major high-power facility for performing this kind of studies and assessing the performance of a fast ADS. The neutronic characterization and burn-up simulations based on MCNP6 code of the reactor core allowed the definition of the geometry and the composition of the fuel assembly and, therefore, the thermal power to be removed. On this basis a thermo-fluid-dynamic assessment, through simple analytical accounts and detailed 3D CFD calculations by OpenFOAM-v1612+ and ANSYS FLUENT v17.0 was made. The present paper is an extended version including the main conclusions and observations emerged in the 2nd AIGE-IIETA International Conference in Genoa.